Exploring Intrapersonal Dialogue in Elderly Living in Nursing Homes to Improve Religious Quality - Eka Putra (Ikatan Sarjana Komunikasi Indonesia, 2026)
This qualitative study employs the theoretical frameworks of intrapersonal communication and gerotranscendence to investigate how intrapersonal dialogue enhances the religious experiences of elderly individuals in nursing homes. The study focuses on Panti Jompo Tresna Werdha Husnul Khatimah in Pekanbaru City, Riau Province, Indonesia. Using a qualitative descriptive approach with in-depth interviews and participatory observation of five purposely selected individuals aged 74–81, as well as thematic analysis, this study aims to understand the mechanisms of spiritual transformation. The findings reveal the complexity of psychospiritual mechanisms through four stages forming a synergistic cycle: adapted sensations through compensation strategies to accept religious stimuli; perceptions transforming the meaning of worship from obligation to existential need; religious memories serving as a source of psychological and spiritual resilience; and reflective thinking processes crystallizing experiences into spiritual maturity. These results reinforce the gerotranscendence theory, which posits that spiritual perspectives evolve in old age and that intrapersonal dialogue serves as a vital coping mechanism. The study concludes that intrapersonal dialogue plays a fundamental and dynamic role in improving the religious lives of the elderly. It also recommends creating a religious environment in nursing homes to support the holistic spiritual health of residents.